- During exercise the body cools itself by sweating. sweating in response to an elevated body temperat... 1 year ago
- Surveys show that people who use calorie information to decide which foods to eat consume on average... 1 year ago
- A(n) _____ competitor provides a product or service that a consumer might buy instead of yours even... 1 year ago
- Tell us about a mistake you've made in your past and what you learned from that mistake. fire fighte... 1 year ago
- You work in an important and visible position in government. your decision is to choose between two... 1 year ago

- What does Mark Twain satirize in this excerpt from "The £1,000,000 Bank-Note"? It was a lovely di... 252 Views 1 year ago
- I need answers for the AYUDAR A LOS DEMÁS UNIT 8 TEST LESSON 6 1. Which of the following is not a... 236 Views 2 years ago
- What unique accomplishment did ruben Dario achieve at the age of 18? A. he graduated from university... 236 Views 1 year ago
- Tyler is a recent college graduate that has a large private student loan debt. He is single with no... 159 Views 1 year ago
- Eudora transferred a balance of $6400 to a new credit card at the beginning of the year. The card of... 118 Views 2 years ago

## Answers

## cocojones

## Best answer

This is a quadratic equation so:

[latex] x^{2} [/latex]- 6x = 7

[latex] x^{2} [/latex]-6x-7=0

then find 2 numbers that satisfy [latex] n_{1} [/latex]+[latex] n_{2} [/latex] = -6 and [latex] n_{1} [/latex]*[latex] n_{2} [/latex] = -7 (where n is one of the numbers)

this works with -1 and 7 (-1 + 7 = 6, -1 * 7 = -7)

so:

[latex] x^{2} [/latex]-6x-7 = (x-1)(x+7)

the awnsers are: -1 and 7

## Jayda

ok so if you have ax^2+bx+c=d to complete the square make sure a=1, if not, dividide everybody by a and since a/a=1, will now equal 1 then move c to other side the take 1/2 of b and square it then add this new number and add it to both sides then factor perfect sqare then take square root of both sides then find x x^2-6x=7 a=1 and c is already on other side take 1/2 of b and square it -6/2=-3 (-3)^2=9 add that to both sides x^2-6+9=7+9 factor perfect square (remember that middle sign is the same sign as b) (x-3)^2=16 squaer root both sides and remember to get the positive and negative root x-3=-4 or 4 2 equations x-3=4 x-3=-4 add 3 to both sides x=7 x=-1 tada